Intellectual capital: an overview / Salwa Muda and Musliha Musman - Muda, Salwa; Musman, Musliha (Universiti Teknologi MARA, Negeri Sembilan, 2022)
Intellectual capital (IC) refers to intangible assets that include knowledge, information, intellectual property, and experience that can be used to create value for a firm. The term “intellectual capital” was first introduced by Galbraith in 1969 who describe IC as an intellectual contribution owned by individuals. Thus, IC is a firms’ collective brainpower and the sum of everything everybody in a company knows that gives it a competitive edge (Stewart (1997). As an intangible asset, even though not captured and reported in financial statements, IC’s role is vital in outlining and enforcing strategies. In particular, IC supports reliance to human and firms’ structures in today’s economic condition. Firms in the new knowledge era are concentrating on the challenging tasks of growing and managing knowledge resources, changing economic and political systems, and increasing stakeholder demands. This has caused firms to be at their competitive advantage to deliver their capabilities through clearly defined strategies to survive in the market. As a result, IC appears as one of the crucial elements in the process of value generation.